Hubungan Pengetahuan Dan Sikap Orang Tua Terhadap Penggunaan Smartphone Dengan Perkembangan Anak Usia 4-6 Tahun Di TK Canggai Putri Kabupaten Karimun - Lisna Kurniawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Currently, the use of smartphones cannot be avoided by early childhood, therefore parents must have good knowledge about the use of smartphones and a good attitude towards the use of smartphones in children where parents have a very important role in supervising children when playing smartphones. Objective: to determine the relationship between parents' knowledge and attitudes towards the use of smartphones with the development of children aged 4-6 years at Canggai Putri Kindergarten, Karimun Regency. Methods: This study used a quantitative design with a cross-sectional approach on 45 respondents using purposive sampling technique and analyzed using Chi-Square. Results: Parents' knowledge of the use of smartphones in children in the good category was 28 respondents (62.2%), parents' attitudes towards the use of smartphones in children were positive as many as 24 respondents (53.3%), children who were in accordance with behavioral and emotional development were 26 children (57.8%). The results of the analysis using Chi Square show that there is no relationship between parental knowledge about the use of smartphones and the development of children aged 4-6 years at Canggai Putri Kindergarten, Karimun Regency (p value = 0.257) and there is a relationship between parental attitudes towards the use of smartphones and the development of children aged 4-6 years at Canggai Putri Kindergarten, Karimun Regency (p value = 0.012), (OR = 4.875). Conclusion: there is a relationship between parental attitudes towards the use of smartphones with the development of children aged 4-6 years at Canggai Putri Kindergarten, Karimun Regency stress and diet with the incidence of hypertension in the karimun tin devotion hospital. Suggestion: In this case, parents should be able to have a good attitude in terms of using smartphones in children, it is intended that children have a limit on both the time and type of application used in order to keep children from becoming addicted to smartphones.